The Role of Corporate Governance in Achieving Firm Value in Manufacturing Firms in Indonesia - Eka Handriani (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study explores the factors influencing firm value in the manufacturing industry in Indonesia, specifically focusing on dividends, investment opportunities, and leverage. The analysis is based on publicly available data from 178 manufacturing companies in Indonesia, spanning the years 2018 to 2023. The primary objective of this research is to identify the key determinants of firm value in Indonesia's manufacturing sector, grounded in capital structure theory, through the development of a theoretical model. The findings indicate that dividend policy, investment decisions, and leverage have a positive impact on firm value within Indonesia's manufacturing industry. This study provides empirical support for both the pecking order theory and agency theory.